2017
DOI: 10.3390/e19050194
|View full text |Cite
|
Sign up to set email alerts
|

Criticality and Information Dynamics in Epidemiological Models

Abstract: Abstract:Understanding epidemic dynamics has always been a challenge. As witnessed from the ongoing Zika or the seasonal Influenza epidemics, we still need to improve our analytical methods to better understand and control epidemics. While the emergence of complex sciences in the turn of the millennium have resulted in their implementation in modelling epidemics, there is still a need for improving our understanding of critical dynamics in epidemics. In this study, using agent-based modelling, we simulate a Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…Many researchers, therefore, have considered information transfer (or causal relationships) among individuals in small groups [37,38,39]. The (local) transfer entropy is the preferred measure to use in this case [40,41,42,43,44,45]. For example, Crosato et al [39] showed that the transfer of misinformation happens in five-fish school when the whole school changes direction.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers, therefore, have considered information transfer (or causal relationships) among individuals in small groups [37,38,39]. The (local) transfer entropy is the preferred measure to use in this case [40,41,42,43,44,45]. For example, Crosato et al [39] showed that the transfer of misinformation happens in five-fish school when the whole school changes direction.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of these embedding parameters followed the method of Garland et al [79] finding the values which maximize the AIS, with the important additional inclusion of bias correction (because increasing k generally serves to increase bias of the estimate) [80]. For several sample σ, γ pairs in both the sub-and supercritical regimes we examined these parameter choices across all regions (up to k, τ ≤ 30), and found the optimal choices to be consistently close to k = 25 and τ = 12 for all variables (for the sampling interval ∆t = 0.5 ms).…”
Section: Active Information Storagementioning
confidence: 99%
“…Code used to generate the data used in this paper can be found at https://github.com/NathanHarding/Thermeff-cont. u = log 10 (ν) (A1) so that du dν = 1 ν log 10 = 10 −u log (10) .…”
Section: Data Accessibilitymentioning
confidence: 99%